2005
DOI: 10.1152/ajpregu.00081.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular dysfunction caused by cecal ligation and puncture is attenuated in CD8 knockout mice treated with anti-asialoGM1

Abstract: The present study was designed to assess hemodynamics and myocardial function at 18 h after injury caused by cecal ligation and puncture (CLP) in CD8-knockout mice treated with anti-asialoGM1 (CD8KO/alphaAsGM1 mice). Arterial pressure was measured by carotid artery cannulation, and left ventricular pressure-volume measurements were obtained by use of a 1.4-Fr conductance catheter. Blood acid-base balance and indexes of hepatic, renal, and pulmonary injury were also measured. CD8KO/alphaAsGM1 mice exhibited hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The presence of severe metabolic acidosis indicates that a state of tissue hypoperfusion exists in wild-type mice after CLP. This is consistent with our previous reports showing that the ultimate mechanism of mortality in wild-type mice after CLP is cardiovascular collapse and shock (25)(26)(27). Treatment of wild-type mice with imipenem did not improve CLP-induced hypothermia and metabolic acidosis, which indicates that systemic infection is not the underlying cause of these alterations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of severe metabolic acidosis indicates that a state of tissue hypoperfusion exists in wild-type mice after CLP. This is consistent with our previous reports showing that the ultimate mechanism of mortality in wild-type mice after CLP is cardiovascular collapse and shock (25)(26)(27). Treatment of wild-type mice with imipenem did not improve CLP-induced hypothermia and metabolic acidosis, which indicates that systemic infection is not the underlying cause of these alterations.…”
Section: Discussionsupporting
confidence: 92%
“…Other potential mechanisms of CLP-induced injury include cecal ischemia and dissemination of bacterial products such as endotoxin and superantigens. There is a high probability that these early mechanisms of injury are mediated or facilitated by CD8 ϩ T and NK cells, because our previous studies showed that depletion of CD8 ϩ T and NK cells is the primary alteration conferring the resistance of ␤2MKO/␣AsGM1 mice to CLPinduced injury (18,26). Mice, such as ␤2MKO/␣AsGM1 mice, which are resistant to these early mechanisms of CLP-induced injury, appear susceptible to infection-associated morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, cardiac output in CLP mice was still significantly decreased compared with that in sham control, suggesting that CLP-induced septic shock results in significant myocardial suppression independent of fluid status. Tao et al (39) have shown that cardiac function was significantly reduced in CLP mice with fluid resuscitation. Albuszies et al (1) reported that a combination of fluid resuscitation and norepinephrine resulted in significantly increased cardiac output in CLP-induced septic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies have shown that myocardial dysfunction is an early and fatal complication of septic shock (11,12,23,39) and that the TLR-4-mediated NF-B activation signaling pathway could be an early molecular event leading to cardiac dysfunction during septic shock (33,40). We have previously shown that GP significantly increased survival in CLP mice (43) and the mechanisms involved downregulating the expression of TLR-4 and blunting NF-B activation in the lung, liver, and spleen (44).…”
Section: Discussionmentioning
confidence: 99%
“…CD8 ϩ T and NK cell-deficient mice show less systemic inflammation, less cardiovascular dysfunction, and fewer physiological derangements after CLP, compared with control mice (8,10). It appears that these cell populations act additively or synergistically because depletion of both cell types provides a level of protection that is greater than that conferred by depletion of either cell type alone (8,9).…”
mentioning
confidence: 99%